1995
DOI: 10.1002/app.1995.070581111
|View full text |Cite
|
Sign up to set email alerts
|

Potassium permanganate/thioureadioxide redox system‐induced grafting of methacrylic acid onto loomstate cotton fabric

Abstract: SYNOPSISGraft polymerization of methacrylic acid (MAA) to loomstate cotton fabric using the KMnO,/thioureadioxide system as the initiator was studied under different polymerization conditions. The polymerization reaction was assessed with respect to graft yield, homopolymer, total conversion, and graft efficiency. The magnitude of each of these characteristics was found to depend upon parameters such as concentrations of KMnO,, thioureadioxide, and MAA as well as liquor ratio, reaction time, and temperature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Thiourea is sensitive to the effect of strong oxidants [7][8][9][10][11][12][13][14][15]. Thus, the oxidation reactions of thioureas into ureas have attracted the interest of chemists for a long time [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiourea is sensitive to the effect of strong oxidants [7][8][9][10][11][12][13][14][15]. Thus, the oxidation reactions of thioureas into ureas have attracted the interest of chemists for a long time [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thiourea is an important industrial chemical product [1][2][3][4][5][6][7]. Animal studies on the chronic toxicity of thiourea have shown that the compound, when administered in drinking water, induces thyroid adenomas and carcinomas in rats [8].…”
Section: Introductionmentioning
confidence: 99%
“…19 Radical induced polymerization technique has been used to crosslink acrylamide with N, N 0 -methylene bisacrylamide. 20,21 AbdelHafiz 22 studied the graft copolymerization of methacrylic acid onto loomstate cotton fabric under different reaction conditions using KMnO 4 / thiourea dioxide system as an initiator. El-Naggar et al 23 used preirradiation technique for graft copolymerizing acrylamide onto Nylon-66.…”
Section: Introductionmentioning
confidence: 99%
“…play an important role in physiological process and industrial production [1][2][3][4][5]. For instance, urea and its alkyl-substituted compounds are often considered as the breaker of water structure [6], the denaturants of native proteins [7] and have a good solubilizing effect on hydrocarbons and polar molecules [8,9].…”
Section: Introductionmentioning
confidence: 99%